2021
DOI: 10.1093/jpepsy/jsab077
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, Telehealth, and Pediatric Integrated Primary Care: Disparities in Service Use

Abstract: Objective The coronavirus disease 2019 pandemic (COVID-19) may increase pediatric mental health needs due to its social, economic, and public health threats, especially among Black, Indigenous, and People of Color and those served within disadvantaged communities. COVID-19 protocols have resulted in increased provision of telehealth in integrated primary care (IPC) but little is known about pediatric telehealth IPC utilization during the pandemic for diverse and traditionally underserved grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…Although implementation of telemedicine holds much promise for greater accessibility of mental health services, our findings demonstrate that the transition to telemedicine in 2020 at both CHOP and BCH reflects what many other academic centers 6 , 7 , 8 , 9 , 10 have found: an exacerbation of racial disparities in overall service utilization. In 2020, clinicians at both CHOP and BCH appears to have seen fewer racially minoritized patients and more white-identifying patients compared to the same period in 2019, albeit the findings emerged at different time points (CHOP within one month and BCH within six months – also acknowledging that findings may have been apparent at one month, but this study may not have been adequately powered to detect such differences at one-month).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Although implementation of telemedicine holds much promise for greater accessibility of mental health services, our findings demonstrate that the transition to telemedicine in 2020 at both CHOP and BCH reflects what many other academic centers 6 , 7 , 8 , 9 , 10 have found: an exacerbation of racial disparities in overall service utilization. In 2020, clinicians at both CHOP and BCH appears to have seen fewer racially minoritized patients and more white-identifying patients compared to the same period in 2019, albeit the findings emerged at different time points (CHOP within one month and BCH within six months – also acknowledging that findings may have been apparent at one month, but this study may not have been adequately powered to detect such differences at one-month).…”
Section: Discussionmentioning
confidence: 59%
“…Another study determined that in pediatric primary care, significant racial disparities existed in telemedicine services – among emergency and chronic visits – following the transition to telemedicine 9 . A recent study from a pediatric integrative primary care practice, that included mental health services, found that Black children were 35% less likely to be scheduled for telemedicine appointments when compared to their white counterparts 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Our data set lacked an indicator for telehealth visits, precluding the assessment of telehealth access as a contributor to care disparities, as previously reported. 19 Finally, Packard Children's Health Alliance represents one health care system; our findings require replication in other health care systems to assess their generalizability.…”
Section: Discussionmentioning
confidence: 91%
“…These disparities were similar to disparities seen in other pediatric and adult studies. [1][2][3][4][21][22][23][24][25][26] Black and Hispanic populations in the United States have faced a long history of systemic racism, originating from foundations in slavery. Structural racism has also permeated the health care system, ranging from mistreatment of Black populations in medical research to racial segregation of hospitals.…”
Section: Discussionmentioning
confidence: 99%